Diet Quality of First Semester Southeastern College Students and the Impact of COVID-19. (7th June 2021) - Yu, Zhiping; Fuglestad, Paul; Gonzalez, Veruska
Abstract: Objectives: Studies have reported poor food choices and unhealthy eating behaviors among college students. The purpose of this study was to assess the diet quality of college freshmen and the impact of the COVID-19 pandemic. Methods: Freshman students 18 years or older in all majors in a southeastern university were invited to take the Diet History Questionnaire III (DHQ III) in fall 2019 and in fall 2020. The Healthy Eating Index (HEI) scores from the participants were obtained and compared to the HEI-2015 national averages through one-sample t-tests. Results: Thirty students in fall 2019 cohort (86.7% female, 46.7% white) and 55 students in fall 2020 cohort (78.2% female, 63.5% white) completed the survey. Compared to national average data, participants in the current study had higher total HEI scores (60.9 vs. 58.3, P  < 0.05), higher total fruits scores (3.8 vs. 2.6, P  < 0.001), higher dairy scores (6.4 vs. 5.4, P  < 0.001), but lower total protein scores (4.1 vs. 5.0, P  < 0.001), lower seafood and plant protein scores (3.6 vs. 5.0, P  < 0.001), higher refined grains scores (8.0 vs. 6.7, P  < 0.001), and higher sodium scores (4.7 vs. 3.4, P  < 0.001). Just examining the 2020 cohort of students, after the onset of the COVID-19 pandemic, the overall HEI scores were lower and not significantly different from the national average ( P  > 0.05) and HEI fatty acids scores were lower (3.7 vs. 4.5, P  < 0.05). Conclusions: The diet quality of freshman college students remains inadequate and interventions are needed to prevent or postpone the health problems especially during the COVID-19 pandemic. Funding Sources: Brooks College of Health, University of North Florida